Hepatitis B and Pregnancy - Ahmed, Faroque (Bangladesh Journal of Medicine, 2024)
Hepatitis B virus (HBV) infection during pregnancy presents with unique management issues for both the mother and the fetus. With a careful, individualized treatment plan, successful pregnancy with healthy offspring can be achieved for women with Chronic Hepatitis B. The risk of developing chronic HBV infection is inversely proportional to the age at time of exposure. The risk is as high as 90 percent in those exposed at birth without vaccination, while the risk is much lower (about 20 to 30 percent) in those exposed during childhood. Maternal screening programs and universal vaccination of infants have significantly reduced transmission rates and are the best way to prevent perinatal HBV infection. Women identified as HBsAg positive during pregnancy should be linked to care for additional testing and determination of need for antiviral therapy. Women who meet standard indications for HBV therapy should be treated. Tenofovirdisoproxil fumarate (TDF) is the preferred choice for this indication. HBV-infected pregnant women with cirrhosis should be managed in high-risk obstetrical practices and treated with TDF to prevent decompensation.The most important risk factors for mother-to-child transmission appear to be a positive HBeAg and/or a high HBV DNA level in the mother. Prevention of mother-to-child transmission is an important component of global efforts to reduce the burden of chronic HBV since vertical transmission is responsible for approximately one-half of chronic infections worldwide. Timely administration of HBV vaccine and HBIG is critical to break the chain of vertical transmission. In settings where HBV DNA or HBeAg testing is available, prophylaxis with TDF is recommended for all HBV-positive pregnant women with HBV DNA ≥200 000 IU/mL or positive HBeAg (preferably from the second trimester of pregnancy until at least delivery or completion of the infant HBV vaccination series), to prevent the mother-to-child transmission (MTCT) of HBV.New recommendation of WHO is - in settings where neither HBV DNA nor HBeAg testing is available, prophylaxis with TDF for all HBV-positive (HBsAg-positive) pregnant women may be considered (preferably from the second trimester of pregnancy until at least delivery or completion of the infant HBV vaccination series), to prevent MTCT of HBV.All interventions should be given in addition to at least three doses of hepatitis B vaccination for all infants, including a timely birth dose. C-section is not indicated owing to insufficient data to support its benefit. Breast feeding is not a contraindication in HBsAg-positive mothers rather should be encouraged to breastfeed their newborns. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 139-140